Pengaruh Ukuran Usaha, Pendidikan, Informasi, Sosialisasi pada Pemahaman UMKM terhadap Laporan Keuangan EMKM - Sulaymah, Vivin; Nugraeni, Nugraeni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to assess the influence of company size and level of education as well as providing information and outreach to MSME players on the preparation of financial reports in accordance with SAK EMKM. The data used is primary data collected through a questionnaire with a Likert scale. This research was carried out in Nogotirto Village, Sleman Regency involving 275 MSMEs registered with the Trade, Operations and Cooperative SMEs Service. The sample was selected using a random sampling technique and calculated using the Slovin formula, so that 74 MSME actors were obtained as a sample. The data analysis techniques used include classical assumption testing and hypothesis testing with the help of IBM SPSS Statistics 25. The research results show that business size and education level do not have a simultaneous influence on MSMEs' understanding of preparing financial reports according to SAK EMKM. However, providing information and outreach has been proven to have a significant positive impact. The implication of these findings is that it is important for MSME players to continue to gain knowledge through relevant information, outreach and training.